Application of 3D printed model for planning the endoscopic endonasal transsphenoidal surgery - Xing Huang (Nature Portfolio, 2021)
Abstract The application of 3D printing in planning endoscopic endonasal transsphenoidal surgery is illustrated based on the analysis of patients with intracranial skull base diseases who received treatment in our department. Cranial computed tomography/magnetic resonance imaging data are attained preoperatively, and three-dimensional reconstruction is performed using MIMICS (Materialise, Leuven, Belgium). Models of intracranial skull base diseases are printed using a 3D printer before surgery. The models clearly demonstrate the morphologies of the intracranial skull base diseases and the spatial relationship with adjacent large vessels and bones. The printing time of each model is 12.52–15.32 h, and the cost ranges from 900 to 1500 RMB. The operative approach was planned in vitro, and patients recovered postoperatively well without severe complications or death. In a questionnaire about the application of 3D printing, experienced neurosurgeons achieved scores of 7.8–8.8 out of 10, while unexperienced neurosurgeons achieved scores of 9.2–9.8. Resection of intracranial skull base lesions is demonstrated to be well assisted by 3D printing technique, which has great potential in disclosing adjacent anatomical relationships and providing the required help to clinical doctors in preoperative planning.